Ontogenetic variability of Bothrops atrox and Bothrops asper snake venoms from Colombia - Saldarriaga Córdoba, Mónica María (2003)
The lancehead snakes Bothrops asper and Bothrops atrox inflict 70–90% of the 3000 bites reported every year in Colombia. In this work, the venoms of B. atrox from Meta (Villavicencio, 33 specimens) and B. asper from Antioquia (San Carlos, 45 specimens), all of them born in captivity, were obtained at different ages (0–6 months; 1, 2 and 3-years old) and compared in terms of their pharmacological and immunochemical characteristics. A conspicuous ontogenetic variability was observed in venom samples from both species. Venoms from newborn and juvenile specimens showed higher lethal, hemorrhagic, edema-forming and coagulant activities, whereas venoms from 3-year old specimens showed higher indirect hemolytic, i.e. phospholipase A2 activity, being more significant in the case of B. asper. SDS-polyacrylamide gel electrophoresis of whole venom for both species evidenced a predominance of high mol. mass bands in the venoms from specimens of <1 year of age, with a change towards bands having lower mol. mass as snakes aged. Gel filtration chromatography showed five peaks in the venoms of B. asper of <6 months and in those from 3-year old specimens. Venom of adult specimens showed a higher number of peaks with indirect hemolytic activity than venom of newborn specimens. Polyvalent antivenom produced in Costa Rica recognized all the bands of both venoms from specimens at all ages tested, when assayed by Western blotting.